Evaluating anxiety and stress coping skills and related variables of mothers with mentally retarded children (Annals of Medical Research, 2021)
Aim: Our aim is to compare the socio-demographic characteristics of mothers with mentally disabled children with those without, and to evaluate anxiety levels and ability of these mothers to cope with stress.
Keywords: Disabled Children; Anxiety; Psychological Status.